IGNITE network: Response of patients to genomic medicine interventions. Issue 5 (20th March 2019) - Orlando, Lori A.; Voils, Corrine; Horowitz, Carol R.; Myers, Rachel A.; Arwood, Meghan J.; Cicali, Emily J.; McDonough, Caitrin W.; Pollin, Toni I.; Guan, Yue; Levy, Kenneth D.; Ramirez, Andrea; Quittner, Alexandra; et al.
Abstract: Background: The IGNITE network funds six genomic medicine projects. Though interventions varied, we hypothesized that synergies across projects could be leveraged to better understand the participant experiences with genomic medicine interventions. Therefore, we performed cross‐network analyses to identify associations between participant demographics and attitudes toward the intervention (attitude), plan to share results (share), and quality of life (QOL). Methods: Data collection for demographics, attitude, share, and QOL surveys were standardized across projects. Recruitment and survey administration varied by each project's protocol. Results: Participants ( N  = 6, 817) were 67.2% ( N  = 4, 584) female, and 37.4% ( N  = 3, 544) were minority. Mean age = 54.0 (sd 14.a). Younger participants were as follows: (1) more positive in attitude pre‐intervention (1.15‐fold decrease/10‐year age increase (OR)) and more negative after (1.14‐fold increase OR); (2) higher in QOL pre‐intervention (1.07‐fold increase OR) and postintervention; (3) more likely to share results (1.12‐fold increase OR). Race was significant when sharing results (white participants increased OR = 1.88), but not for change in QOL pre–postintervention or attitude. Conclusion: Our findings demonstrate the feasibility of this approach and identified a few key themes which are as follows: age was consistently significant across the three outcomes, whereas race had less of an impact than expected. However, these are only associations and thus warrant further study. Abstract : The IGNITE network performed a cross‐network analysis for the six genomic medicine demonstration projects looking at the relationship of participant demographics and participant survey responses. The outcomes include participant quality of life, plan to share the results of the genomic medicine intervention, and attitude toward the genomic medicine intervention.